2020
DOI: 10.3389/fendo.2019.00880
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term Ketogenic Diet Impairs Markers of Bone Health in Response to Exercise

Abstract: Objectives: To investigate diet-exercise interactions related to bone markers in elite endurance athletes after a 3.5-week ketogenic low-carbohydrate, high-fat (LCHF) diet and subsequent restoration of carbohydrate (CHO) feeding. Methods: World-class race walkers (25 male, 5 female) completed 3.5-weeks of energy-matched (220 kJ•kg•d −1) high CHO (HCHO; 8.6 g•kg•d −1 CHO, 2.1 g•kg•d −1 protein, 1.2 g•kg•d −1 fat) or LCHF (0.5 g•kg•d −1 CHO, 2.1 g•kg•d −1 protein, 75-80% of energy from fat) diet followed by acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 27 publications
1
57
0
1
Order By: Relevance
“…For example, supplementation with exogenous ketone products to achieve similarly high levels has been shown to alter metabolism and enhance performance in one study [76], although this has been a singular fining [77][78][79][80]. Neither can we be sure that chronic CHO restriction will not exacerbate the impairments to the interaction of exercise with body systems such as the immune system [81], bone remodeling [82] and iron metabolism [83] seen with acute episodes of low CHO availability, or interfere with long term training quality by reducing the capacity to undertake higher-intensity workouts. Therefore, longer-term studies are welcomed but require careful control so that extraneous factors are removed.…”
Section: Plos Onementioning
confidence: 99%
“…For example, supplementation with exogenous ketone products to achieve similarly high levels has been shown to alter metabolism and enhance performance in one study [76], although this has been a singular fining [77][78][79][80]. Neither can we be sure that chronic CHO restriction will not exacerbate the impairments to the interaction of exercise with body systems such as the immune system [81], bone remodeling [82] and iron metabolism [83] seen with acute episodes of low CHO availability, or interfere with long term training quality by reducing the capacity to undertake higher-intensity workouts. Therefore, longer-term studies are welcomed but require careful control so that extraneous factors are removed.…”
Section: Plos Onementioning
confidence: 99%
“…Thus, a KD conceivably may be a plausible nutritional strategy in specific scenarios, such as: i) during prolonged low-intensity events predominantly reliant on fat oxidation to fuel exercise; ii) during the pre-competition carbohydrate-restriction phase prior to bodybuilding and/or physique competitions when it is advantageous to restrict carbohydrate intake; and/or iii) for individuals who prefer to lowcarbohydrate diets [14]. However, recent studies indicate that adherence to KD may impair training adaptations and require additional study [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Often, athletes competing at elite levels are susceptible to bone injury, partly due to dietary factors such as low energy availability and/or the strenuous nature of the exercise program. A recent study conducted by Heikura et al [ 24 ] investigated the effects of a KD on bone health among a group of elite-level race walkers. After a 3-week intervention period, this study found that athletes had increased markers of bone resorption (+22% CI 9, 35%) and decreased markers of bone formation (−14% CI −19, −9), when compared to baseline values.…”
Section: Discussionmentioning
confidence: 99%